THE INNOVATION OF THE MA'ARIF NAHDLATUL ULAMA EDUCATION SYSTEM IN THE DIGITALIZATION ERA IN BENGKULU - Juliansyah Juliansyah (Conciencia, 2021)
The phenomena demonstrate that various changes have occurred in the digitization era, including paradigm shifts, changing needs, and policy shifts. These changes have an impact on the traditional system of a nation, particularly in Indonesia. The aim of this research is to discover the innovation of the Ma'arif Nahdlatul Ulama education system in the digitalization era in Bengkulu Province. A qualitative research method was applied in this study. The administrators of the Ma'arif Educational Institution in Bengkulu Province and the administrators at the Branch institution, the Nahatul 'Ulam' Management in the Regional section and Branch administrators, NU figures, principals of schools/madrasas under the Ma'arif Educational Institution's coordination, and religious figures in Bengkulu Province were the subjects of this study. The findings revealed that the Ma'arif NU education system innovated in all aspects of education, including aims, curriculum, learning methods, and models, educators and education staff, and institution kinds and management.The fact that can be seen is the growing development of Ma'arif NU educational institutions at the Elementary School/Madrasah Ibtidai'yah and Madrasah Aliyah (MA) levels, as well as Vocational High Schools (SMK) to universities. The conclusion is that the Ma'arif Nahdlatul Ulama education system's ideas, thoughts, and reforms considerably contribute to being a reference for those who are struggling in the world of Islamic education.